NATURAL AND GEOGRAPHICAL DESCRIPTION OF THE SOUTHERN FERGANA CANAL (Scientific journal of the Fergana State University, 2025)
This article provides information about the history and geographical features of the South Fergana Canal. The South Fergana Canal, which is the object of my research, is one of the largest irrigation canals flowing through the Fergana Valley. The South Fergana Canal flows through the territory of the Republics of Uzbekistan and Kyrgyzstan. Based on the characteristics of the canal, observation points were determined.